(untitled) (Global Journal of Human-Social Science, 2023)
The Universalization Fund for Telecommunications Services Fust was designed in 2000 to provide public investments to expand services in areas that needed to be better covered by the telecom carries However since its creation the fund lacks effectiveness The study seeks to evaluate this public policy and explain the practically non-existent results and impacts until now Our contribution is to structure this public policy using a logic model and the program theory of change to understand and evaluate the fund s regulatory design The analysis recognizes that the recent changes in Fust s legislation have improved its architecture and governance following suggestions from the international literature on universalization funds Nonetheless some additional regulatory adjustments are suggested such as creating more restrictive mechanisms to block or reallocate the fund s revenues keeping its steering committee active discussing new sources of revenue and improving communication and transparency